Perancangan Dan Pengembangan Vıdeo Company Profıle PT Asukı Batam - Deli Deli; Donny Zhang (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
PT Asuki Batam was established on February 24, 2006, the location of PT Asuki Batam is located in the Tanah Mas Blok K Complex No. 3 Sei Panas, Batam. PT Asuki Batam is a shop engaged in the marketing of local auto parts and accessories and CBU. This activity aims to introduce PT Asuki Batam to the public to know the services, services and distribution materials in PT Asuki Batam and give tangible results. Introducing PT Asuki Batam by making a promotional video that is Company Profile using Adobe Premiere Pro CC 2018 and published on Youtube, Data collection methods used: observation, interview, and library studies with the process of designing development, preproduction, production, postproduction, and delivery. Advice for business owners pt Asuki Batam, is expected to be active in the introduction and promotion by using social media or the internet in various social media platforms.